Advances in Heat Transfer Enhancement - Saha, Sujoy Kumar; Tiwari, Manvendra; Sundén, Bengt; Wu, Zan (Springer International Publishing : Imprint: Springer, 2016)
This Brief addresses the phenomena of heat transfer enhancement. A companion edition in the SpringerBrief Subseries on Thermal Engineering and Applied Science to three other monographs including "Critical Heat Flux in Flow Boiling in Microchannels," this volume is idea for professionals, researchers, and graduate students concerned with electronic cooling.